Morphological Features of Lymphoid Structures of the Small Intestine of Rats in Norm and Chronic Radiation Sickness - Khasanova Dilnoza Ahrorovna (Journal of Coastal Life Medicine, 2023)
The amount of Grouped Lymph Nodes (GLN) in irradiated rats decreases, the number of nodules in them and the size of the GLN increase relatively from the initial part of the small intestine to the final. The shape of the GLN after irradiation varies from oval to round and irregular. The number of single nodules increases. GLN covers an average of 2.1% of the small intestine of irradiated rats, as opposed to a healthy 2.8% of the small intestine. These facts indicate a decrease in the functional activity of intestinal lymphoid tissue after exposure to chronic radiation.